Economic contributions of wild fisheries and aquaculture: A social accounting matrix (SAM) analysis for Gyeong-Nam Province, Korea. (15th April 2020) - Kim, Do-Hoon; Seung, Chang K.
Abstract: This study quantifies and compares the economic contributions of two alternative methods of producing raw fish – wild fisheries and aquaculture – in Gyeong-Nam (GN) province, Korea. This study departs from most previous studies in several important ways. First, this study employs a social accounting matrix (SAM) model to overcome the inability of input-output (IO) models to address the distributional effects. Second, this study conducts a regional-level analysis rather than a national-level analysis. Third, this study uses an adjusted demand-driven SAM modeling framework to avoid double-counting problem with the conventional Leontief demand-driven model and the problem with Ghosh (1958) approach. Results indicate that the contributions per unit of output from the two different fish producing industries to total provincial employee compensation and total provincial business surplus are substantially different, but that the contributions (per unit of output) to total provincial output, total household income, and provincial government revenue are not significantly different between the two different fish producing industries. Results also reveal that the non-seafood industries that benefit most from wild fisheries are starkly different from those that gain most from aquaculture. Graphical abstract: Image 1 Highlights: A social accounting matrix (SAM) model was developed for seafood industries. Economic contributions of wild fisheries and aquaculture were quantified. An adjustment to the SAM model was made to measure the contributions.